Synthesis, Characterization and Potential of Pt-Ru Supported Carbon Nanocage (CNC) for Methanol Oxidation Reaction (MOR) and DMFC Application - Che Ramli, Zatil Amali; Kamarudin, Siti Kartom; Mohd Zainoodin, Azran; Basri, Sahriah (International Journal of Integrated Engineering, 2019)
In this article, a new type of support which is carbon nanocage have been introduced and synthesized by pyrolysis method using MgO metal as the template of carbon nanocage (CNC). Three types of polymers which are PANi, PPy and PVAc as carbon source have been chosen for the CNC production that synthesized at temperature range 600-900 oC, under nitrogen gas flow. All synthesized CNC were characterized using TEM to study their morphologies. From TEM characterization, the best CNC will be doped with Pt-Ru catalyst for further study. From XRD analysis, the particle size of Pt-Ru/CNC is smaller than Pt-Ru/C. Meanwhile, in electrochemical evaluation of cyclic voltammetry, the Pt-Ru/CNC electrocatalyst shows higher ECSA value than Pt-Ru/C, which are 16.9 and 6.2 m2 g-1, respectively, which is more than 1.7 times higher. In addition, from characterization the CNC support and Pt-Ru/CNC shows high BET surface area, and smaller particle size. Lastly, it can be said that Pt-Ru supported CNC is an ideal candidate for future DMFC anode electrocatalyst.